A Visuo-Haptic Framework for Object Recognition Inspired by Human Tactile Perception - Ghazal Rouhafzay; Ana-Maria Cretu (Proceedings, 2019)
This paper addresses the issue of robotic haptic exploration of 3D objects using an enhanced model of visual attention, where the latter is applied to obtain a sequence of eye fixations on the surface of objects guiding the haptic exploratory procedure. According to psychological studies, somatosensory data resulting as a response to surface changes sensed by human skin are used in combination with kinesthetic cues from muscles and tendons to recognize objects. Drawing inspiration from these findings, a series of five sequential tactile images are obtained by adaptively changing the size of the sensor surface according to the object geometry for each object, from various viewpoints, during an exploration process. We take advantage of the contourlet transform to extract several features from each tactile image. In addition to these somatosensory features, other kinesthetic inputs including the probing locations and the angle of the sensor surface with respect to the object in consecutive contacts are added as features. The dimensionality of the large feature vector is then reduced using a self-organizing map. Overall, 12 features from each sequence are concatenated and used for classification. The proposed framework is applied to a set of four virtual objects and a virtual force sensing resistor array (FSR) is used to capture tactile (haptic) imprints. Trained classifiers are tested to recognize data from new objects belonging to the same categories. Support vector machines yield the highest accuracy of 93.45%.